Game location and team quality effects on performance profiles in professional soccer - Lago-Penas, C.; Lago-Ballesteros, J. (Journal of Sports Science & Medicine, 2011)
Home advantage in team sports has an important role in determining the outcome of a game. The aim of the present study was to identify the soccer game- related statistics that best discriminate home and visiting teams according to the team quality. The sample included all 380 games of the Spanish professional men's league. The independent variables were game location (home or away) and the team quality. Teams were classified into four groups according to their final ranking at the end of the league. The game-related statistics registered were divided into three groups: (i) variables related to goals scored; (ii) variables related to offense and (iii) variables related to defense. A univariate (t-test and Mann-Whitney U) and multivariate (discriminant analysis) analysis of data was done. Results showed that home teams have significantly higher means for goal scored, total shots, shots on goal, attacking moves, box moves, crosses, offsides committed, assists, passes made, successful passes, dribbles made, successful dribbles, ball possession, and gains of possession, while visiting teams presented higher means for losses of possession and yellow cards. In addition, the findings of the current study confirm that game location and team quality are important in determining technical and tactical performances in matches. Teams described as superior and those described as inferior did not experience the same home advantage. Future research should consider the influence of other confounding variables such as weather conditions, game status and team form.